Fenomena Over Education dan Under Education Dalam Pasar Kerja Wanita Sumatera Barat - Yadewani, Doris (Jurnal Ekonomi, 2013)
This paper analyzes the phenomenon of over-education and under-education in the labor market women in West Sumatra. The phenomenon of over-education and under-education is a phenomenon where a workforce with higher education levels occupy jobs that are not in accodance with the level of education. And reverse, eith a lower level of education actually occupy a higher job. This study uses the data SUSENAS 2009 for the province of West Sumatra. Form the result of the study showed, in an over-educaion and under-educationin the labor market and women in West Sumatra there are significant revenue relationship to the phenomenon of over-education and under-education in the labor market women in West Sumatra. From the reseach, it is necessery to link and macth between women's education and labor market in the formal sector needs a policy that directed the education of women in accordance with the demand of women in the labo market such as improving access and quality in vocational education and diploma in accordance with the culture of women's skills and the need to standardize education policy, employment and wage position. Policy where labor exploitation through unfair wage system for workers needs to be done so that the phenomenon of over-education and under-education will have a positive impact for the company and the workers concerned.